Revolutionserinnerung in der Frühen Neuzeit Refigurationen der 'Glorious Revolution' in Großbritannien (1688-1760) - Niggemann, Ulrich (Veröffentlichungen des Deutschen Historischen Instituts London/ Publications of the German Historical Institute London, 2017)
This study focuses on the 1688-89 "Glorious Revolution" to examine the commemoration of revolution in 18th century Great Britain. A key emphasis is placed on how the Revolution impacted and informed sociopolitical debate. The study illuminates the struggle over the accepted interpretation of the Revolution, and reveals how this struggle reconfigured historical narratives.